COVID-19 : How Will European Banks Fare? - Aiyar, Shekhar (Departmental Papers; Departmental Paper, 2021)
This paper evaluates the impact of the crisis on European banks' capital under a range of macroeconomic scenarios, using granular data on the size and riskiness of sectoral exposures. The analysis incorporates the important role of pandemic-related policy support, including not only regulatory relief for banks, but also policies to support businesses and households, which act to shield the financial sector from the real economic shock.